Ethical Approaches in Research Practice - Donev, Dejan (Studia Universitatis Babeş-Bolyai, 2015)
High standards of ethics provide a higher quality of research and increase substantially its social impact. They promote research integrity and better alignment of research with community needs and expectations. The author’s intention is to determine the current position and the application of the current ethical approaches in research practice in terms of the development of common international research space with a “transparent and universally harmonized standards” on European soil.
Abordări etice în practica cercetării
Keywords: ethics, research, approaches, European soil.